2008
DOI: 10.1111/j.1365-2966.2008.13979.x
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of minor mergers - I. General properties of thick discs

Abstract: We present simulations of the formation of thick discs via the accretion of two-component satellites onto a pre-existing thin disc. Our goal is to establish the detailed characteristics of the thick discs obtained in this way, as well as their dependence on the initial orbital and internal properties of the accreted objects. We find that mergers with 10-20 per cent mass of the host lead to the formation of thick discs whose characteristics are similar, both in morphology as in kinematics, to those observed. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
334
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 301 publications
(364 citation statements)
references
References 104 publications
30
334
0
Order By: Relevance
“…Another possibility is that thick discs are created through the heating of preexisting thin discs by minor mergers (Di Matteo et al 2011;Villalobos & Helmi 2008). Evidence for merger encounters can be found in the phasespace structure of Milky Way disc stars (e.g., Gómez et al 2013Gómez et al , 2012bMinchev et al 2009).…”
Section: The Galactic Thick Discmentioning
confidence: 99%
See 2 more Smart Citations
“…Another possibility is that thick discs are created through the heating of preexisting thin discs by minor mergers (Di Matteo et al 2011;Villalobos & Helmi 2008). Evidence for merger encounters can be found in the phasespace structure of Milky Way disc stars (e.g., Gómez et al 2013Gómez et al , 2012bMinchev et al 2009).…”
Section: The Galactic Thick Discmentioning
confidence: 99%
“…The largest source is most likely satellite-disc interactions (e.g., Bournaud et al 2009;Villalobos & Helmi 2008), which have been found to increase an initially constant scale-height by up to a factor of ∼ 10 in 3-4 disc scalelengths. We showed in the left row of Fig.…”
Section: Migration Suppresses Disc Flaring When Infalling Satellites mentioning
confidence: 99%
See 1 more Smart Citation
“…Another possibility is that thick disks are created through the heating of preexisting thin disks with the help of mergers (Quinn et al 1993;Villalobos & Helmi 2008;Di Matteo et al 2011), whose rate decreases with decreasing redshift. Evidence for satellite-disk encounters can be found in structure in the phase-space of MW disk stars (e.g., Minchev et al 2009;Gómez et al 2013Gómez et al , 2012c, which can last for as long as ∼4 Gyr (Gómez et al 2012a).…”
Section: Thick-disk Formation Scenariosmentioning
confidence: 99%
“…For example, they can induce changes that move late-type spiral galaxies towards earlier Hubble types and contribute to the thickening and heating of the stellar disk (Quinn et al 1993;Walker et al 1996;Velazquez & White 1999;Font et al 2001;Benson et al 2004;Kazantzidis et al 2008). The disks of galaxies are generally not fully destroyed by these events, and a remaining kinematically cold and thin component containing ∼15 to 25% of the initial stellar disk mass can indeed survive, embedded in a hotter and thicker disk (e.g., Villalobos & Helmi 2008), whereas the presence of gas in the disk galaxy can largely prevent the destruction of its thin stellar disk (Moster et al 2010).…”
Section: Introductionmentioning
confidence: 99%